Family Resilience in Implementing Parenting in Sandwich Generation Families (Phenomenological Study on Sandwich Generation Families in Sumberpucung Village) - Arimbi, Devinta Dwiky; Dayati, Umi; Wahyuni, Sri (Universitas Negeri Padang, 2023)
Living as a sandwich generation can enable one to feel overwhelmed by the double roles they're playing. The burden of foster care in the sandwich generation family is the feelings experienced by caregivers referring to emotional, physical, social, and financial conditions and affecting personal, family, and social lives. This method of research uses qualitative research with a model of phenomenological approach and uses data collection techniques such as observation, interview and documentation techniques. First, the physical health burden arises from the exhaustion of childcare and work. Second, the mental health burdens arise from financial problems and poor social stereotypes about women who work remotely. Third, the financial burden emerges from the abundance of needs to be met so that the sandwich generation has no savings. Fourthly, the burden of social life is because the busy working sandwich generation is less able to communicate with their families. Family resilience. First, the physical economic endurance of the family's sandwich generation meets primary needs by working. This work is done by a couple of sandwich generations to meet the needs of the family. Second, social resilience where the family of the sandwich generation always implants religious values as well as building effective communication with family members. Third, the psychological resilience of the way the family deals with problems in a quiet and calming way.